Implementasi Metode Ward Dan Peppard Dalam Perencanaan Strategis Sistem Informasi Studi Kasus PT XYZ - Herdadi, Anintyo (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
PT XYZ needs information system (SI) strategic planning to increase efficiency, effectiveness and competitiveness in providing services to customers. This research uses the Ward and Peppard methodology with three stages: input (identification of vision/mission and data collection), analysis (analysis of the business environment and IS), and output (mission formulation, IS/IT strategy, and IS management strategy). The research results show that the use of appropriate technology and the development of reliable information systems are key factors for the company's success. To support performance in the next three years, it is recommended to implement CRM (customer relationship management) and ERP (enterprise resource planning) systems which are able to increase operational efficiency and provide competitive advantages.